2015
DOI: 10.1088/0964-1726/24/12/125030
|View full text |Cite
|
Sign up to set email alerts
|

Sliding mode fault detection and fault-tolerant control of smart dampers in semi-active control of building structures

Abstract: Recent decades have witnessed much interest in the application of active and semi-active control strategies for seismic protection of civil infrastructures. However, the reliability of these systems is still in doubt as there remains the possibility of malfunctioning of their critical components (i.e. actuators and sensors) during an earthquake. This paper focuses on the application of the sliding mode method due to the inherent robustness of its fault detection observer and faulttolerant control. The robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…In this study, the simple Bouc‐Wen model shown in Figure is used to accurately predict the behavior of a shear‐mode MR damper over a wide range of inputs . The equations governing force f predicted by this model are as follows(): -78ptf=c0truex˙+αz4pt truez˙=normalγ||x˙zzn1normalβtruex˙zn+Atruex˙, …”
Section: Numerical Modeling Of Mr Dampersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the simple Bouc‐Wen model shown in Figure is used to accurately predict the behavior of a shear‐mode MR damper over a wide range of inputs . The equations governing force f predicted by this model are as follows(): -78ptf=c0truex˙+αz4pt truez˙=normalγ||x˙zzn1normalβtruex˙zn+Atruex˙, …”
Section: Numerical Modeling Of Mr Dampersmentioning
confidence: 99%
“…The model parameters depend on voltage v to the current driver as follows(): normalα=αa+αbu 2ptc0=c0a+c0bu, …”
Section: Numerical Modeling Of Mr Dampersmentioning
confidence: 99%
“…Traditional building base-isolation systems are designed to shift the structural resonant frequencies to a range that is well below the frequencies of ground motions during earthquakes [1,2]. To ensure a significant reduction of vibration transmitted to a building over the isolation range which covers the frequencies of the estimated earthquake ground motions, low horizontal-stiffness bearings are fitted into the isolation layer of the building.…”
Section: Introductionmentioning
confidence: 99%
“…A control system usually refers to control algorithms (e.g., active control, semi‐active control, hybrid control, and passive control) and the corresponding controlling devices (e.g., semi‐control hydraulic dampers and active‐control piezoelectric actuators). Among various control algorithms, semi‐active control systems exhibit their attractive characteristics, including less power, higher reliability, and particularly higher adaptability for earthquake events, as compared to their counterparts . As a result, semi‐active control systems and the associated devices have played an important role in structural vibration controls and mitigations.…”
Section: Introductionmentioning
confidence: 99%
“…Among various control algorithms, semi-active control systems exhibit their attractive characteristics, including less power, higher reliability, and particularly higher adaptability for earthquake events, as compared to their counterparts. [25,26,[28][29][30][31] As a result, semi-active control systems and the associated devices have played an important role in structural vibration controls and mitigations.…”
Section: Introductionmentioning
confidence: 99%